Satellite-Based Observations Reveal the Altitude-Dependent Patterns of SIFyield and Its Sensitivity to Ambient Temperature in Tibetan Meadows - Ruonan Chen; Liangyun Liu; Xinjie Liu (Remote Sensing, 2021)
Photosynthesis and its sensitivity to the changing environment in alpine regions are of great significance to the understanding of vegetation–environment interactions and other global ecological processes in the context of global change, while their variations along the elevation gradient remain unclear. Using solar-induced chlorophyll fluorescence (SIF) derived from satellite observations, we discovered an increase in solar-induced fluorescence yield (<semantics>SIFyield</semantics>) with rising elevation in Tibetan meadows in the summer, related to the altitudinal variation in temperature sensitivity at both seasonal and interannual scales. Results of the altitudinal patterns of <semantics>SIFyield</semantics> demonstrated higher temperature sensitivity at high altitudes, and the sensitivity at the interannual scale even exceeds that at seasonal scale when the elevation reaches above 4700 m. This high-temperature sensitivity of <semantics>SIFyield</semantics> at high altitudes implies potential adaptation of alpine plants and also indicates that changes in photosynthesis-related physiological functions at high altitudes should receive more attention in climate change research. The altitudinal <semantics>SIFyield</semantics> patterns revealed in this study also highlight that variations in temperature sensitivity should be considered in models, otherwise the increasing trend of <semantics>SIFyield</semantics> observations can never be discovered in empirical simulations.